Governança de dados: proposta de um framework conceitual para os órgãos de segurança pública do Distrito Federal - Silva, Rodrigo Teixeira da (2023)
Data Governance (DG) has become a topic of outstanding importance in modern organizations, since the amount and complexity of data generated and stored has increased exponentially in recent decades. In this context, an effective GD becomes essential to guarantee the quality, reliability and security of information. This dissertation, through a literature review and research methodologies: content analysis and document analysis, identified 55 DG mechanisms in the literature review and sought evidence of their application in a sample of Government Constitutive Acts. For the selection of the sample, a survey was carried out on the World Wide Web in January 2023, where 12 documents were selected, 5 Normative Acts establishing policies and GD committees, within the scope of the Federal Public Administration (FPA) and 7 Acts Normative, in the context of the Government of the Federal District (GFD), which address the issue of data management and apply to the public security bodies of the FD (PSB). As main results, it was possible to identify 169 GD mechanisms in the governmental context, yet, it was found that 76% of the mechanisms contained in the literature are present in the Constitutive Acts. Based on these mechanisms, it was possible to present a conceptual framework for Government Data Governance (GDG) applied to PSB. The GDG subordinated to public governance was represented through the mechanisms of leadership, strategy and control; the interaction between the PSB and the 169 GDG mechanisms distributed in four dimensions: Governance, Quality, Management and Compliance. It is expected that the proposed framework will serve as a reference for future research on GDG and allow both the PSB and other GFD Bodies to implement the GDG mechanisms that are most appropriate to their realities.